2021
DOI: 10.3390/jcm10102150
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Increases the Incidence of Upper Respiratory Tract Symptoms among Polish Children

Abstract: A substantial proportion of airway disease’s global burden is attributable to exposure to air pollution. This study aimed to investigate the association between air pollution, assessed as concentrations of particulate matter PM2.5 and PM10 on the upper respiratory tract symptoms (URTS) in children. A nation-wide, questionnaire-based study was conducted in Poland in winter 2018/2019 in a population of 1475 children, comparing URTS throughout the study period with publicly available data on airborne particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…This is preferred in particular in the types of sociological surveys where it is difficult to specify all of the members of the basic group (e.g., the population), but it is possible to determine basic statistical characteristics that are assumed to correlate with the variables being ascertained [105]. This is a quasi-representative method that, if performed correctly, achieves similar results to probability sampling methods [106], as the sample can be assumed to represent the entire population under investigation [107]. The economic, time, and staffing merits of this type of sampling were used [108], a method that has become one of the most widely used in sociological research due to its benefits [109,110].…”
Section: Methodsmentioning
confidence: 99%
“…This is preferred in particular in the types of sociological surveys where it is difficult to specify all of the members of the basic group (e.g., the population), but it is possible to determine basic statistical characteristics that are assumed to correlate with the variables being ascertained [105]. This is a quasi-representative method that, if performed correctly, achieves similar results to probability sampling methods [106], as the sample can be assumed to represent the entire population under investigation [107]. The economic, time, and staffing merits of this type of sampling were used [108], a method that has become one of the most widely used in sociological research due to its benefits [109,110].…”
Section: Methodsmentioning
confidence: 99%
“…In children aged 3–12 years old, the prevalence of upper respiratory tract symptoms such as a runny nose, sneezing and cough was positively associated with high 12-week mean PM 2.5 and PM 10 concentrations [ 70 ]. The difference between the frequency of symptoms between the control and the most polluted regions was about 10% [ 70 ].…”
Section: Childrenmentioning
confidence: 99%
“…In children aged 3–12 years old, the prevalence of upper respiratory tract symptoms such as a runny nose, sneezing and cough was positively associated with high 12-week mean PM 2.5 and PM 10 concentrations [ 70 ]. The difference between the frequency of symptoms between the control and the most polluted regions was about 10% [ 70 ]. Moreover, Wrotek et al reported that paediatric hospitalizations due to respiratory syncytial virus infections in Poland were significantly associated with a rise in either PM 2.5 , PM 10 or NO 2 concentrations [ 71 ].…”
Section: Childrenmentioning
confidence: 99%
“…Lagged concentrations of PM exposure in Japan were associated with cough in asthmatic people, and even stronger associations were noted among those without asthma, with indications of a dose–response relationship [ 23 ]. Moderate levels of PM exposure were linked with increased risk of upper respiratory tract infections in Poland [ 24 ]. PM concentrations measured by backpack monitors in the Bronx, New York City, USA were associated with decreased lung function in schoolchildren [ 25 ].…”
Section: Introductionmentioning
confidence: 99%